2023
DOI: 10.1094/mpmi-10-22-0208-fi
|View full text |Cite
|
Sign up to set email alerts
|

Realizing the Full Potential of Advanced Microscopy Approaches for Interrogating Plant-Microbe Interactions

Abstract: Microscopy has served as a fundamental tool for insight and discovery in plant-microbe interactions for centuries. From classical light and electron microscopy to corresponding specialized methods for sample preparation and cellular contrasting agents, these approaches have become routine components in the toolkit of plant and microbiology scientists alike to visualize, probe and understand the nature of host-microbe relationships. Over the last three decades, three-dimensional perspectives led by the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 129 publications
0
1
0
Order By: Relevance
“…In addition to imaging plant roots themselves, the ability to simultaneously image microbes in the rhizosphere, the region in the vicinity of the roots where the microbiome interacts with the plant, would help understand the complex mechanisms through which root-microbe interactions impact plant growth 50,51 . We found that THG can be combined with 3P fluorescence to simultaneously image plant roots and bacteria as well as fungi in the rhizosphere in situ .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to imaging plant roots themselves, the ability to simultaneously image microbes in the rhizosphere, the region in the vicinity of the roots where the microbiome interacts with the plant, would help understand the complex mechanisms through which root-microbe interactions impact plant growth 50,51 . We found that THG can be combined with 3P fluorescence to simultaneously image plant roots and bacteria as well as fungi in the rhizosphere in situ .…”
Section: Resultsmentioning
confidence: 99%
“…Electron microscopy has become a routine method to visualize, elucidate, and probe the nature of host-pathogen relationships (Czymmek et al, 2023;Łotocka et al, 2023). Changes occurring in the dynamic plant-pathogen system suggested altered cellular functions due to biotic stress (Park, 2006).…”
Section: Introductionmentioning
confidence: 99%